Description of Stereoscopic Vision Between Amblyopia And Emmetropia Eyes In Students At Kuta Bakmee Aceh Besar Public Elementary School - Hajar, Siti; Sakdiah, Sakdiah; D Multazam, Muhammad (Journal of Neonatal Surgery, 2025)
Amblyopia is a decrease in vision in a person's eyes even though it has been corrected with the best vision correction which cannot be related to structural abnormalities of the eye or visual axis. The state of amblyopia in children can cause binocular vision disorders resulting in decreased stereoscopic vision function. This study aims to determine the stereoscopic vision between amblyopia and emmetropia in students at Kuta Bakmee Aceh Besar Elementary School. This research is a descriptive observational study with a cross-sectional design that looks at stereoscopic vision between amblyopia and emmetropia based on visual acuity results. The research sample was selected by non-probability sampling method using total sampling. The results showed that the characteristics of the research subjects were mostly male students, namely 62 students (58. 40%) and the 8 years old group (28%). Most research subjects were emmetropes with fine stereoscopic vision, namely 105 students (99.1%) and research subjects who were amblyopia with gross stereoscopic vision were found to be 1 student (0.9%).